The Main Directions of Strategic Tourism Development in Uzbekistan - Toychievna, Alieva Makhbuba; kizi, Islamova Nasiba Adkham (European Journal of Life Safety and Stability (2660-9630), 2023)
This article provides information on the tourism sector in Uzbekistan and Topic: the main directions of strategic development of the tourism sector in Uzbekistan.